Conventional and organic farms with more intensive management have lower soil functionality. - van Rijssel, Sophie Q.; Koorneef, Guusje J.; Veen, G. F. (Ciska); Pulleman, Mirjam; de Goede, Ron G. M.; Comans, Rob N.J.; van der Putten, Wim H.; Mason-Jones, Kyle (AAAS, 2025)
Organic farming is often considered to be more sustainable than conventional farming. However, both farming systems comprise highly variable management practices. In this study, we show that in organic and conventional arable fields, the multifunctionality of soils decreases with increasing agricultural management intensity. Soil organic carbon content and bacterial biomass, respectively, were the strongest abiotic and biotic predictors of soil multifunctionality. Greater soil multifunctionality was associated with less-frequent inversion tillage and higher frequency of grass-legume cover cropping, and organic farming did not outperform conventional farming. Our results suggest that reducing management intensity will enhance soil multifunctionality in both conventional and organic farming. This implies that, in contexts where high-yielding, high-intensity agriculture prevails, the paradigm of sustainable intensification should be replaced by "productive deintensification."